Esophagectomy for esophageal stricture with systemic sclerosis: a case report - Yuho Ebata; Yasue Kimura; Kentaro Nonaka; Sho Nambara; Qingjiang Hu; Ryota Nakanishi; Tomonori Nakanoko; Mitsuhiko Ota; Eiji Oki; Tomoharu Yoshizumi (Surgical Case Reports, 2023)
Abstract Background Systemic sclerosis (SSc) is an autoimmune disease characterized by frequent esophageal involvement. However, there are few reports on esophagectomy for esophageal strictures associated with SSc. Herein, we present a case of successful treatment of an esophageal stricture associated with SSc through subtotal esophagectomy. Case presentation A 53-year-old female patient was diagnosed with SSc, interstitial pneumonia, and gastroesophageal reflux disease (GERD). The patient developed an esophageal ulcer and benign stricture that required a subtotal esophagectomy 10 years after the diagnosis. Histopathological findings revealed thinning of the muscle layer, a characteristic feature of SSc. The patient was free of dysphagia or regurgitation. Conclusions An esophagectomy is a valuable option for treating esophageal strictures in SSc. Therefore, surgical approaches should be established for patients with SSc.